Interface transmittance and interface waves in acoustic Willis media - Qu, Hongfei; Liu, Xiaoning; Zhang, Anfu (Frontiers in Physics, 2023)
Acoustics Willis media, also known as bianisotropic acoustic media, incorporate additional coupling between pressure and velocity, and between momentum and volumetric strain in their constitutive equation. The extra coupling terms have significant influence on the acoustic wave behavior. In this paper, the unusual wave phenomena relevant to interfaces in between homogeneous acoustic Willis media are theoretically studied. We show that Willis media offer more flexible control in wave front and energy flow when waves are transmitted through an interface. Different with traditional acoustic fluid, Willis acoustic media are found to support edge and interface waves, for which the existence conditions and corresponding wave features are systematically investigated. The study unveils more possibilities for manipulating acoustic wave, and may inspire new functional designs with acoustic Willis metamaterials.